find the value of a and b
Attachments:
![](https://hi-static.z-dn.net/files/da1/6ffa8f0e280d010a9fd7bb1a85652d7b.jpg)
Answers
Answered by
5
Hey buddy!!
here is yr answer....
![= > \frac{ \sqrt{3} + 1 }{ \sqrt{3} - 1 } = a + b \sqrt{3} \\ \\rationalise \: the \: denominator \\ \\ = > \frac{ \sqrt{3} + 1}{ \sqrt{3} - 1} \times \frac{ \sqrt{3} + 1}{ \sqrt{3} + 1 } = a + b \sqrt{3} \\ \\ = > \frac{( \sqrt{3} + 1)^{2} }{( \sqrt{3 } - 1)( \sqrt{3} + 1) } = a + b \sqrt{3} \\ \\ = > \frac{3 + 2 \sqrt{3} + 1 }{3 - 1} = a + b \sqrt{3} \\ \\ = > \frac{4 + 2 \sqrt{3} }{2} = a + b \sqrt{3} \\ \\ = > \frac{2(2 + \sqrt{3}) }{2} = a + b \sqrt{3} \\ \\ = > 2 + \sqrt{3} = a + b \sqrt{3} \\ \\ = > 2 + 1 \sqrt{3} = a + b \sqrt{3} = > \frac{ \sqrt{3} + 1 }{ \sqrt{3} - 1 } = a + b \sqrt{3} \\ \\rationalise \: the \: denominator \\ \\ = > \frac{ \sqrt{3} + 1}{ \sqrt{3} - 1} \times \frac{ \sqrt{3} + 1}{ \sqrt{3} + 1 } = a + b \sqrt{3} \\ \\ = > \frac{( \sqrt{3} + 1)^{2} }{( \sqrt{3 } - 1)( \sqrt{3} + 1) } = a + b \sqrt{3} \\ \\ = > \frac{3 + 2 \sqrt{3} + 1 }{3 - 1} = a + b \sqrt{3} \\ \\ = > \frac{4 + 2 \sqrt{3} }{2} = a + b \sqrt{3} \\ \\ = > \frac{2(2 + \sqrt{3}) }{2} = a + b \sqrt{3} \\ \\ = > 2 + \sqrt{3} = a + b \sqrt{3} \\ \\ = > 2 + 1 \sqrt{3} = a + b \sqrt{3}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7B+%5Csqrt%7B3%7D+%2B+1+%7D%7B+%5Csqrt%7B3%7D+-+1+%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5Crationalise+%5C%3A+the+%5C%3A+denominator+%5C%5C++%5C%5C+++%3D++%26gt%3B++%5Cfrac%7B+%5Csqrt%7B3%7D++%2B+1%7D%7B+%5Csqrt%7B3%7D++-+1%7D++%5Ctimes++%5Cfrac%7B+%5Csqrt%7B3%7D++%2B+1%7D%7B+%5Csqrt%7B3%7D+%2B+1+%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5C++%3D++%26gt%3B+++%5Cfrac%7B%28+%5Csqrt%7B3%7D+%2B+1%29%5E%7B2%7D++%7D%7B%28+%5Csqrt%7B3+%7D+-+1%29%28+%5Csqrt%7B3%7D++%2B+1%29+%7D+%3D+a+%2B+b+%5Csqrt%7B3%7D+++%5C%5C++%5C%5C++%3D++%26gt%3B++%5Cfrac%7B3+%2B+2+%5Csqrt%7B3%7D+%2B+1+%7D%7B3+-+1%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5C++%3D++%26gt%3B++%5Cfrac%7B4+%2B+2+%5Csqrt%7B3%7D+%7D%7B2%7D++%3D+a+%2B+b++%5Csqrt%7B3%7D++%5C%5C++%5C%5C++%3D++%26gt%3B++%5Cfrac%7B2%282+%2B++%5Csqrt%7B3%7D%29+%7D%7B2%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5C++%3D++%26gt%3B+2+%2B++%5Csqrt%7B3%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5C++%3D++%26gt%3B+2+%2B+1+%5Csqrt%7B3%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D+)
Therefore, a = 2 , b = 1
Hope it hlpz.
here is yr answer....
Therefore, a = 2 , b = 1
Hope it hlpz.
Anonymous:
mark her answer as brainalest
Answered by
5
Heya friend,
Here is the answer you were looking for:
Identities used :
![{(a + b)}^{2} = {a}^{2} + {b}^{2} + 2ab \\ (a + b)(a - b) = {a}^{2} - {b}^{2} {(a + b)}^{2} = {a}^{2} + {b}^{2} + 2ab \\ (a + b)(a - b) = {a}^{2} - {b}^{2}](https://tex.z-dn.net/?f=+%7B%28a+%2B+b%29%7D%5E%7B2%7D++%3D++%7Ba%7D%5E%7B2%7D++%2B++%7Bb%7D%5E%7B2%7D++%2B+2ab+%5C%5C+%28a+%2B+b%29%28a+-+b%29+%3D++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D+)
![\frac{ \sqrt{3} + 1 }{ \sqrt{3} - 1 } = a + b \sqrt{3} \\ \frac{ \sqrt{3} + 1 }{ \sqrt{3} - 1 } = a + b \sqrt{3} \\](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B3%7D+%2B+1++%7D%7B+%5Csqrt%7B3%7D+-+1+%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C+)
On rationalizing the denominator we get,
![= \frac{ \sqrt{3} + 1}{ \sqrt{3} - 1} \times \frac{ \sqrt{3} + 1}{ \sqrt{3} + 1} \\ \\ = \frac{ {( \sqrt{3}) }^{2} + {(1)}^{2} + 2( \sqrt{3} )(1)}{ {( \sqrt{3}) }^{2} - {(1)}^{2} } \\ \\ = \frac{3 + 1 + 2 \sqrt{3} }{3 - 1} \\ \\ \frac{4 + 2 \sqrt{3} }{2} \\ \\ = \frac{2(2 + \sqrt{3} )}{2} \\ \\ = 2 + \sqrt{3} \\ = \frac{ \sqrt{3} + 1}{ \sqrt{3} - 1} \times \frac{ \sqrt{3} + 1}{ \sqrt{3} + 1} \\ \\ = \frac{ {( \sqrt{3}) }^{2} + {(1)}^{2} + 2( \sqrt{3} )(1)}{ {( \sqrt{3}) }^{2} - {(1)}^{2} } \\ \\ = \frac{3 + 1 + 2 \sqrt{3} }{3 - 1} \\ \\ \frac{4 + 2 \sqrt{3} }{2} \\ \\ = \frac{2(2 + \sqrt{3} )}{2} \\ \\ = 2 + \sqrt{3} \\](https://tex.z-dn.net/?f=+%3D++%5Cfrac%7B+%5Csqrt%7B3%7D++%2B+1%7D%7B+%5Csqrt%7B3%7D++-+1%7D++%5Ctimes++%5Cfrac%7B+%5Csqrt%7B3%7D++++%2B++1%7D%7B+%5Csqrt%7B3%7D+++%2B++1%7D++%5C%5C++%5C%5C+++%3D++%5Cfrac%7B+%7B%28+%5Csqrt%7B3%7D%29+%7D%5E%7B2%7D+%2B++%7B%281%29%7D%5E%7B2%7D+++%2B+2%28+%5Csqrt%7B3%7D+%29%281%29%7D%7B+%7B%28+%5Csqrt%7B3%7D%29+%7D%5E%7B2%7D+-++%7B%281%29%7D%5E%7B2%7D++%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B3+%2B+1+%2B+2+%5Csqrt%7B3%7D+%7D%7B3+-+1%7D++%5C%5C++%5C%5C++%5Cfrac%7B4+%2B+2+%5Csqrt%7B3%7D+%7D%7B2%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B2%282+%2B++%5Csqrt%7B3%7D+%29%7D%7B2%7D++%5C%5C++%5C%5C++%3D+2+%2B++%5Csqrt%7B3%7D++%5C%5C+)
On comparing we get,
![2 + \sqrt{3} = a + b \sqrt{3} \\ \\ a = 2 \: : \: b = 1 2 + \sqrt{3} = a + b \sqrt{3} \\ \\ a = 2 \: : \: b = 1](https://tex.z-dn.net/?f=2+%2B++%5Csqrt%7B3%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5C+a+%3D+2+%5C%3A++%3A++%5C%3A+b+%3D+1)
Hope this helps!!!
Feel free to ask in the comment section if you have any doubt regarding to my answer...
@Mahak24
Thanks...
☺☺
Here is the answer you were looking for:
Identities used :
On rationalizing the denominator we get,
On comparing we get,
Hope this helps!!!
Feel free to ask in the comment section if you have any doubt regarding to my answer...
@Mahak24
Thanks...
☺☺
Similar questions